2020
DOI: 10.1126/science.aba6098
|View full text |Cite
|
Sign up to set email alerts
|

An orally available non-nucleotide STING agonist with antitumor activity

Abstract: Pharmacological activation of the STING (stimulator of interferon genes)–controlled innate immune pathway is a promising therapeutic strategy for cancer. Here we report the identification of MSA-2, an orally available non-nucleotide human STING agonist. In syngeneic mouse tumor models, subcutaneous and oral MSA-2 regimens were well tolerated and stimulated interferon-β secretion in tumors, induced tumor regression with durable antitumor immunity, and synergized with anti–PD-1 therapy. Experimental and theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
285
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(339 citation statements)
references
References 36 publications
7
285
1
Order By: Relevance
“…In a recent study in Science, Pan et al 1 identified an orally available non-nucleotide human stimulator of interferon genes (STING) agonist, MSA-2 (benzothiophene oxobutanoic acid), with excellent safety tolerance in vivo. The noncovalently tethered dimers of MSA-2 could bind STING with nanomolar affinity, and the acidic tumor microenvironment would substantially increase the cell entry and retention of MSA-2 and its dimerized interaction with STING, thus leading to a superior antitumor potency of combined MSA-2 and anti-PD-1 treatments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study in Science, Pan et al 1 identified an orally available non-nucleotide human stimulator of interferon genes (STING) agonist, MSA-2 (benzothiophene oxobutanoic acid), with excellent safety tolerance in vivo. The noncovalently tethered dimers of MSA-2 could bind STING with nanomolar affinity, and the acidic tumor microenvironment would substantially increase the cell entry and retention of MSA-2 and its dimerized interaction with STING, thus leading to a superior antitumor potency of combined MSA-2 and anti-PD-1 treatments.…”
mentioning
confidence: 99%
“…The developed agonist not only resolved the challenge of drug administration but also extended the therapeutic potentials toward solid tumors. In this follow-up study, Pan et al 1 developed a unique STING agonist, MSA-2, that displayed tumor targeting and could be administrated orally.…”
mentioning
confidence: 99%
“…In 2018, diABZI was discovered as a new class of synthetic small molecule STING receptor agonist with much higher potency than CDNs and suitable for systemic administration ( Ramanjulu et al, 2018 ). Recently, an orally available non-nucleotide STING agonist, MSA-2, was reported to have favorable activity and tolerability profiles ( Pan et al, 2020a ). Further optimization of these molecules for improved safety margins may still be needed for their clinical application against coronavirus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, in cases where it is hard to predict the compound binding site, a library of compounds or fragments (see Section 2.3) can be screened against the purified protein target [12,13]. In some cases, the target is overexpressed in a cell system, or cells are engineered for a target-specific readout, blurring the line between target-based screening and phenotypic approaches as discussed below [14,15].…”
Section: Target-based Approachesmentioning
confidence: 99%
“…For example, phenotypic screens have been very powerful to identify compounds that inhibit cellular signaling pathways, such as Hedgehog [18], Wnt [19,20], STING [14], and NFκB [21] signaling. Signaling pathways are complex cellular protein networks essential for communication between cells, establishing, e.g., proper embryonic development, tissue homeostasis, and immune response, and much of the associated biology remains to be unraveled.…”
Section: Phenotypic Screensmentioning
confidence: 99%